Synthesis of (−)‐menthol: Industrial synthesis routes and recent development - Dylong, Dominik; Hausoul, Peter J. C.; Palkovits, Regina; Eisenacher, Matthias (Flavour and fragrance journal, 2022)
(−)‐Menthol is one of the most popular aroma compounds worldwide. While in the past mostly extracted from mint plants, today (−)‐menthol synthesis from other raw materials is becoming more relevant. Common starting materials for menthol synthesis are m‐cresol, citral and myrcene, but also substrates like menthone, mono‐ and bicyclic terpenes and terpenoids have been used for this purpose in the past. As for many applications (−)‐menthol of high purity is required, asymmetric syntheses and enantiomeric resolution of obtained raw products are applied for menthol production. This review gives an overview on the most important synthetic menthol production processes of the companies Symrise, Takasago and BASF and relevant literature in the field of menthol synthesis with a focus on the last 20 years. A review on the synthesis of (−)‐menthol from various raw materials, including the main industrial processes of the companies Symrise, Takasago and BASF and recent literature on this topic.